Support for people with dementia. Issue 12 (December 2019) - Kotecha, Anish; Phelps, Kerry
Dementia costs the UK economy over £26.3 billion a year. Although dementia is a progressive and often terminal condition, people typically survive for many years after diagnosis. People affected by dementia and their families can struggle in understanding the changes that occur in daily living and will often turn to their GPs for support. This article outlines the problems that people with dementia can face and the organisations and other sources of support that can help right from the outset.